Generador de estrategias de locomoción para una cadena articulada - Hernández, Monica L. (Pontificia Universidad Javeriana, 2015)
An articulated chain has the ability to generate the diversity of movement to navigate through difficult terrain for conventional robots with wheels. It is very important to know the dynamic model of an articulated chain, with the dynamic model is able to control the type of movement that has the robot, involving different variables such as position, velocity, energy that will measure the performance of these movements, therefore, will improve these movements. In this research proposal will be presented a dynamic model for a chain of 16-DOF articulated using the Newton Euler recursive algorithm.